Adjuvant sunitinib or sorafenib for high-risk, non-metastatic renal-cell carcinoma (ECOG-ACRIN E2805): a double-blind, placebo-controlled, randomised, phase 3 trial. Issue 10032 (14th May 2016) - Haas, Naomi B; Manola, Judith; Uzzo, Robert G; Flaherty, Keith T; Wood, Christopher G; Kane, Christopher; Jewett, Michael; Dutcher, Janice P; Atkins, Michael B; Pins, Michael; Wilding, George; Cella, David; et al.
Summary: Background: Renal-cell carcinoma is highly vascular, and proliferates primarily through dysregulation of the vascular endothelial growth factor (VEGF) pathway. We tested sunitinib and sorafenib, two oral anti-angiogenic agents that are effective in advanced renal-cell carcinoma, in patients with resected local disease at high risk for recurrence. Methods: In this double-blind, placebo-controlled, randomised, phase 3 trial, we enrolled patients at 226 study centres in the USA and Canada. Eligible patients had pathological stage high-grade T1b or greater with completely resected non-metastatic renal-cell carcinoma and adequate cardiac, renal, and hepatic function. Patients were stratified by recurrence risk, histology, Eastern Cooperative Oncology Group (ECOG) performance status, and surgical approach, and computerised double-blind randomisation was done centrally with permuted blocks. Patients were randomly assigned (1:1:1) to receive 54 weeks of sunitinib 50 mg per day orally throughout the first 4 weeks of each 6 week cycle, sorafenib 400 mg twice per day orally throughout each cycle, or placebo. Placebo could be sunitinib placebo given continuously for 4 weeks of every 6 week cycle or sorafenib placebo given twice per day throughout the study. The primary objective was to compare disease-free survival between each experimental group and placebo in the intention-to-treat population. All treated patients with at least one follow-up assessment were included in the safety analysis. This trial is registered withClinicalTrials.gov, numberNCT00326898 . Findings: Between April 24, 2006, and Sept 1, 2010, 1943 patients from the National Clinical Trials Network were randomly assigned to sunitinib (n=647), sorafenib (n=649), or placebo (n=647). Following high rates of toxicity-related discontinuation after 1323 patients had enrolled (treatment discontinued by 193 [44%] of 438 patients on sunitinib, 199 [45%] of 441 patients on sorafenib), the starting dose of each drug was reduced and then individually titrated up to the original full doses. On Oct 16, 2014, because of low conditional power for the primary endpoint, the ECOG-ACRIN Data Safety Monitoring Committee recommended that blinded follow-up cease and the results be released. The primary analysis showed no significant differences in disease-free survival. Median disease-free survival was 5·8 years (IQR 1·6–8·2) for sunitinib (hazard ratio [HR] 1·02, 97·5% CI 0·85–1·23, p=0·8038), 6·1 years (IQR 1·7–not estimable [NE]) for sorafenib (HR 0·97, 97·5% CI 0·80–1·17, p=0·7184), and 6·6 years (IQR 1·5–NE) for placebo. The most common grade 3 or worse adverse events were hypertension (105 [17%] patients on sunitinib and 102 [16%] patients on sorafenib), hand-foot syndrome (94 [15%] patients on sunitinib and 208 [33%] patients on sorafenib), rash (15 [2%] patients on sunitinib and 95 [15%] patients on sorafenib), and fatigue (110 [18%] patients on sunitinib and 44 [7%] patients on sorafenib). There were five deaths related to treatment or occurring within 30 days of the end of treatment; one patient receiving sorafenib died from infectious colitis while on treatment and four patients receiving sunitinib died, with one death due to each of neurological sequelae, sequelae of gastric perforation, pulmonary embolus, and disease progression. Revised dosing still resulted in high toxicity. Interpretation: Adjuvant treatment with the VEGF receptor tyrosine kinase inhibitors sorafenib or sunitinib showed no survival benefit relative to placebo in a definitive phase 3 study. Furthermore, substantial treatment discontinuation occurred because of excessive toxicity, despite dose reductions. These results provide a strong rationale against the use of these drugs for high-risk kidney cancer in the adjuvant setting and suggest that the biology of cancer recurrence might be independent of angiogenesis. Funding: US National Cancer Institute and ECOG-ACRIN Cancer Research Group, Pfizer, and Bayer.